Self-other differences in social mindfulness: beliefs about other people's selfishness are grounded in one's own selfish impulses - Simão, Cláudia (2023)
There is a robust tendency for people to expect others to be more immoral than them, for instance, more selfish. Where do these pessimistic beliefs come from? We explore a socio-metacognitive account whereby those beliefs originate in one's own impulses to act selfishly. In two studies, we used the social mindfulness paradigm, a task that provides the initial chooser the opportunity to be socially mindful about other people or not. Results show 1) that people expect others to be more selfish than them, and 2) that this belief in the selfishness of others is related to one's own impulses to act selfishly. Thus, even when people are kind in their choices, they tend to be less generous in their beliefs about the kindness of others, and this is particularly the case when those selfless choices did not come easily to them, but rather required suppressing an impulse to act selfishly.